Packaging material and electronic device module containing the same

By using polyolefin compositions with cage silsesquioxane bridge agents with multiple isolated double bonds in solar cell systems, the refractive index and crosslinking of the encapsulated material are improved, and the incident light utilization of the encapsulated material is solved The problem of low rate enhances the efficiency of solar cells.

CN115725251BActive Publication Date: 2024-12-31HANGZHOU FIRST APPLIED MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110991383.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-26
Publication Date
2024-12-31
Estimated Expiration
2041-08-26

AI Technical Summary

Technical Problem

In existing solar photovoltaic power generation systems, the incidence of incident light of the packaging materials is low, resulting in optical loss and reduced efficiency.

Method used

Using an encapsulation material made of polyolefin compositions, the material comprises a cage-type silsesquioxane bridge agent with multiple isolated double bonds through which organic inorganic nanohexalogies are formed during the polyolefin crosslinking process The structure is improved, the refractive index is improved, and the cross-linking reaction is promoted through photoinitiators and peroxides.

Benefits of technology

The refractive index and crosslinking degree of the packaging material are improved, the viscosity migration of the bridge agent is reduced, the bonding performance is enhanced, and the incident light utilization rate and overall performance of the solar cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115725251B_ABST
    Figure CN115725251B_ABST
Patent Text Reader

Abstract

The present invention discloses a packaging material and an electronic device module containing the same. The packaging material is prepared from a polyolefin composition, which includes a polyolefin resin and a bridging agent, and the bridging agent has a structure shown in the general formula (I): #imgabs0# wherein n1, n2, n3, n4, n5, n6, n7, and n8 are integers of 0 to 6, respectively. The bridging agent used in the packaging material of the present invention is a type of polysilsesquioxane with a three-dimensional structure and multiple isolated double bonds. The bridging agent can not only enable the polyolefin material to achieve sufficient crosslinking, but also overcome the technical problem in the prior art that the bridging agent has high viscosity and is easily precipitated from the packaging material to the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photoelectric conversion devices, and in particular to a packaging material and an electronic device module comprising the same. Background Art

[0002] Clean energy accounts for an increasing proportion in the energy structure of major countries in the world. Among them, solar photovoltaic power generation has developed rapidly because it is safe, reliable, noise-free, pollution-free, renewable, and its cost is close to or even lower than that of thermal power generation. In recent years, "double-sided double-glass" solar panels are being adopted by more and more power station owners due to their high reliability and ability to achieve double-sided power generation. "Double-sided double-glass" panels have front tempered glass, back tempered glass, solar cells, and packaging materials that seal the solar cells between the front tempered glass and the back tempered glass.

[0003] Generally, it is hoped that the transmittance of the packaging material will be increased to increase the luminous flux of the incident light. The transmittance of the conventional packaging material ethylene-vinyl acetate EVA (VA content of 28wt% and above) can often reach about 92.5% (380-1100nm range) after full cross-linking, but the transmittance of the conventional coated glass can reach more than 94%. The transmittance of the packaging material and the transmittance of the coated glass are not proportional, resulting in optical loss. On the other hand, the refractive index of glass is 1.5, and the refractive index of the silicon nitride material on the surface of the cell is 2.0. After theoretical calculation, the refractive index of the packaging material between the two is the square root of the product of the two, that is, 1.73, when the interface light reflection reaches the minimum value, that is, the utilization rate of the incident light is maximized. The refractive index of the commonly used packaging materials EVA or POE materials is between 1.48 and 1.50, and improving the refractive index of the packaging material has become a research topic. Summary of the invention

[0004] The present invention aims to provide a packaging material and an electronic device module containing the same to solve the problem of low incident light utilization rate. After in-depth research, the inventor surprisingly found that a cage-type silsesquioxane with a double bond at the end group can not only be used as a bridging agent to crosslink polyolefin polymers, but also, with its nano-sized and rigid core, forms an organic-inorganic nano-hybrid structure in the process of participating in the crosslinking process with polyolefin, thereby improving the refractive index of polyolefin.

[0005] According to one aspect of the present invention, a packaging material is provided. The packaging material is prepared from a polyolefin composition, the polyolefin composition includes a polyolefin resin and a bridging agent, and the bridging agent has a structure shown in general formula (I):

[0006] General formula (I),

[0007] Here, n1, n2, n3, n4, n5, n6, n7, and n8 are each independently an integer of 0 to 6.

[0008] Furthermore, n1, n2, n3, n4, n5, n6, n7, and n8 are each independently 0 or 1.

[0009] Furthermore, in the polyolefin composition, based on 100 parts by weight of the polyolefin resin, the mass content of the bridging agent relative to the polyolefin resin is 0.05% to 3%.

[0010] Furthermore, the polyolefin resin is a homopolymer or copolymer of an alpha olefin having less than 20 carbon atoms, and the copolymer is a random copolymer or block copolymer of two or more alpha olefins having less than 20 carbon atoms; preferably, the alpha olefin having less than 20 carbon atoms is ethylene, propylene, butene, pentene, hexene, heptene or octene.

[0011] Furthermore, the polyolefin resin is ethylene acetate copolymer (EVA), wherein the VA content is 20wt% to 40wt%.

[0012] Furthermore, the melting point of the polyolefin resin is 40 to 100° C.; the melt index of the polyolefin resin is 1 to 30 g / 10 min.

[0013] Furthermore, the polyolefin composition further comprises an initiator, and the amount of the initiator is 0.1 to 1 part by weight based on 100 parts by weight of the polyolefin resin.

[0014] Further, the initiator includes a photoinitiator or a peroxide.

[0015] Furthermore, based on 100 parts by weight of the polyolefin resin, the polyolefin composition further comprises 0.1 to 0.8 parts by weight of a tackifier.

[0016] Further, the adhesion promoter is a silane coupling agent having at least one ethylenically unsaturated group and at least one hydrolyzable group.

[0017] Furthermore, the polyolefin composition further comprises an auxiliary agent, wherein the auxiliary agent is one or more selected from the group consisting of a light stabilizer, an antioxidant, an ultraviolet absorber, a plasticizer, a pigment and a filler.

[0018] According to another aspect of the present invention, an electronic device module is provided, which comprises an electronic component and one or more layers of packaging material, wherein the packaging material is any of the above packaging materials.

[0019] Furthermore, the electronic component is a solar cell.

[0020] Furthermore, the packaging material is a packaging film, and the thickness of the packaging film is 0.1 mm to 1 mm.

[0021] Furthermore, the encapsulation material is an encapsulation film, and the encapsulation film is an uncrosslinked film or a pre-crosslinked film. When the encapsulation film is a pre-crosslinked film, the pre-crosslinking degree of the pre-crosslinked film is 1% to 80%.

[0022] The bridging agent used in the packaging material of the present invention is a type of polysilsesquioxane with a three-dimensional structure and multiple isolated double bonds. This bridging agent can not only enable the polyolefin material to achieve sufficient cross-linking, but also overcome the technical problem in the prior art that the bridging agent has high viscosity and is easy to precipitate from the packaging material to the surface; in addition, this type of bridging agent also has a bonding effect, so it is particularly suitable for polyolefin packaging materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0024] Figure 1 A schematic diagram showing the structure of an electronic device module in an embodiment of the present invention is shown; and

[0025] Figure 2 A schematic structural diagram of an electronic device module in another embodiment of the present invention is shown. DETAILED DESCRIPTION

[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0027] Aiming at the technical problem that the bridging agent in the prior art has high viscosity and is easy to precipitate from the packaging material to the surface, the inventors have found a type of cage-type siloxane bridging agent with multiple isolated double bonds after intensive research. This bridging agent can not only enable the polyolefin material to achieve sufficient crosslinking, but also overcome the technical problem that the bridging agent in the prior art has high viscosity and is easy to precipitate from the packaging material to the surface; in addition, this type of bridging agent also has a bonding effect, so it is particularly suitable for polyolefin packaging materials. The siloxane with multiple isolated double bonds provided by the present invention is a polyene compound with polysilsesquioxane (POSS) as the core.

[0028] According to a typical embodiment of the present invention, a packaging material is provided. The packaging material is prepared from a polyolefin composition, the polyolefin composition includes a polyolefin resin and a bridging agent, and the bridging agent has a structure shown in general formula (I):

[0029] General formula (I),

[0030] Wherein, n1, n2, n3, n4, n5, n6, n7, n8 are each independently an integer of 0 to 6, preferably, n1, n2, n3, n4, n5, n6, n7, n8 have the same value; preferably, n1, n2, n3, n4, n5, n6, n7, n8 are each independently 0 or 1. If n=0, the group connected to Si is a vinyl group, and if n=1, the group connected to Si is an allyl group.

[0031] Preferably, in the polyolefin composition, the mass content of the bridging agent relative to the polyolefin resin is 0.05% to 3%, preferably 0.1% to 2%, more preferably 0.2% to 1.5%, further preferably 0.3% to 1.2%, and further preferably 0.4% to 1%, based on 100 parts by weight of the polyolefin resin. Within this ratio range, the polyolefin resin can be fully crosslinked. Typically, the polyolefin resin is a homopolymer or copolymer of an alpha olefin having a carbon number of less than 20 (for example, ethylene, propylene, butene, pentene, hexene, heptene or octene, etc.), and the copolymer is a random copolymer or block copolymer of two or more alpha olefins having a carbon number of less than 20; typically, the polyolefin resin is ethylene-vinyl acetate (EVA), wherein the VA content is 20wt%-40wt%.

[0032] In one embodiment of the present invention, the melting point of the polyolefin resin is 40-100° C., and the melt index of the polyolefin resin is 1-30 g / 10 min (190° C., 2.16 kg) as determined by the peak temperature of the endothermic peak of a differential scanning calorimeter (DSC).

[0033] In another embodiment of the present invention, an electronic device module is provided. The electronic device module comprises an electronic component and one or more layers of packaging material, which is any of the above-mentioned packaging materials. Generally, the cross-sectional view of the electronic device is shown in Figure 1, and the electronic device module is formed into an integral module by vacuum hot pressing of a front cover plate, a rear substrate, an electronic component, and one or more layers of packaging material.

[0034] According to a typical embodiment of the present invention, the electronic device to which the electronic device module belongs is a solar cell. For example, it can be a solar cell assembly. In the solar cell, preferably, the packaging material is a packaging film, and the thickness of the packaging film is 0.1 mm to 1 mm.

[0035] The polyolefin composition provided by the present invention can be uncrosslinked or pre-crosslinked. When it is pre-crosslinked, the pre-crosslinking degree is 1% to 80%, and the pre-crosslinking is achieved by electron beam irradiation, X-ray, gamma ray or ultraviolet irradiation and other technical means known in the industry.

[0036] In order to allow the polyolefin resin to be fully cross-linked, the polyolefin composition provided by the present invention further comprises a free radical initiator. The amount of the free radical initiator used is 0.1 to 1 part by weight based on 100 parts by weight of the polyolefin resin.

[0037] Wherein, the free radical initiator refers to a free radical that can form active free radicals under energy input such as light and heat, thereby initiating a crosslinking reaction of the polymer. In the polyolefin composition for forming the adhesive film provided in the present application, the free radical initiator includes a photoinitiator and a peroxide. Adding the photoinitiator and the peroxide to the polyolefin composition at the same time is conducive to improving the reactivity of the polyolefin composition, thereby further improving its crosslinking degree, and then improving the comprehensive performance of the adhesive film.

[0038] The above-mentioned photoinitiator and peroxide can be selected from the commonly used types in this application. Preferably, the photoinitiator includes but is not limited to benzophenone, benzanthrone, benzoin, benzoin alkyl ether, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, p-phenoxydichloroacetophenone, 2-hydroxyisopropyl-phenyl ketone, 1-phenylpropanedione-2-(ethoxycarbonyl)oxime, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide ( TPO), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide ( 819), 2,2-dimethoxy-1,2-diphenylacetophenone ( 651), 2-ethoxy-1,2-diphenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, 2-hydroxycyclohexyl phenyl ketone ( 184), 2-Hydroxyisopropylphenyl ketone ( 1173), 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone ( 2959), 2-methyl-1-(4-methylmercaptophenyl)-morpholine-1-propanone ( 907) and 2-phenyl-2,2-dimethylamino-1-(4-morpholinophenyl)-1-butanone ( 369). Preferably, the peroxide includes, but is not limited to, one or more mixtures of diacyl peroxide, dialkyl peroxide, peroxyester, and peroxyketal. Among these organic peroxides, tert-butyl peroxybenzoate, tert-amyl peroxybenzoate, tert-butyl peroxyacetate, tert-amyl peroxyacetate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-amyl peroxy-3,5,5-trimethylhexanoate, 2,5-dimethyl-2,5-bis(benzoylperoxy)-hexane, tert-butyl peroxyisopropyl carbonate, tert-butyl peroxide-2-ethylhexyl carbonate, tert-amyl peroxide-2-ethylhexyl carbonate, tert-amyl peroxyisobutyrate, ethyl 3,3-bis(tert-butylperoxy)butyrate, ethyl 3,3-bis(tert-amylperoxy)butyrate, n-butyl 4,4-bis(tert-butylperoxy)valerate, 2,2-bis(tert-butylperoxy)butane, 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane. Among them, tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxy-3,5,5-trimethylhexanoate, and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane are preferred.

[0039] In a preferred embodiment, the polyolefin composition further comprises 0.1 to 0.8 parts by weight of a tackifier based on 100 parts by weight of the polyolefin resin. The amount of the tackifier includes but is not limited to the above range, and limiting it within the above range is beneficial to further improve the adhesion between the film and the substrate. More preferably, based on 100 parts by weight of the polyolefin resin, the polyolefin composition comprises 0.15 to 0.6 parts by weight of the tackifier, and further preferably, based on 100 parts by weight of the polyolefin polymer resin, the polyolefin composition comprises 0.2 to 0.5 parts by weight of the tackifier.

[0040] The above-mentioned tackifier can be selected from the commonly used types in the art. In a preferred embodiment, the tackifier is a silane coupling agent with at least one ethylenically unsaturated group and at least one hydrolyzable group. The introduction of olefinic groups can chemically bind the tackifier to the polymer, and the introduction of hydrolyzable groups (such as methoxy or ethoxy) can make the tackifier bond to the substrate or electronic device during heating. More preferably, each ethylenically unsaturated group is independently selected from vinyl, allyl or γ-(methyl) acryloyloxypropyl, and each hydrolyzable group is independently selected from methoxy or ethoxy; The tackifier is selected from one or more of the group consisting of γ-methacryloyloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane and allyltriethoxysilane.

[0041] In order to further improve the comprehensive performance of the film, some additives may be added to the above composition. In a preferred embodiment, the above additives include one or more of the group consisting of light stabilizers, antioxidants, ultraviolet absorbers, plasticizers, pigments and fillers.

[0042] Among them, the light stabilizer is used to improve the stability of the packaging film under long-term ultraviolet radiation. Preferably, the light stabilizer is a hindered amine compound. More preferably, the above-mentioned light stabilizer includes but is not limited to bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis (1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 4- (methyl) acryloxy-2,2,6,6-tetramethyl piperidine and α-olefin monomers The graft copolymer obtained by polymerization, 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, 3,5-di-tert-butyl-4-hydroxy-benzoic acid hexadecyl ester, sebacate bis-2,2,6,6-tetramethylpiperidinol and tris (1,2,2,6,6-pentamethyl-4-piperidinyl) phosphite is composed of one or more. In order to further improve the light stability of the film, preferably, based on 100 parts by weight of the polyolefin resin, the amount of the light stabilizer in the above composition is 0.02 to 0.8 parts by weight, preferably 0.05 to 0.6 parts by weight, and more preferably 0.1 to 0.5 parts by weight.

[0043] Antioxidants are used to improve the stability of polymer extrusion processing, as well as long-term and use, and to delay degradation due to the action of heat and oxygen. In a preferred embodiment, the antioxidant is a hindered phenol compound and / or a phosphite compound. Compared with other antioxidants, the above antioxidants have better stability and antioxidant properties. More preferably, hindered phenol compounds include but are not limited to 2,6-di-tert-butyl-4-ethylphenol, 2,2'-methylene-bis-(4-methyl-6-tert-butylphenol), 2,2'-methylene-bis-(4-ethyl-6-tert-butylphenol), 4,4'-butylene-bis-(3-methyl-6-tert-butylphenol), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 7-octadecyl-3-(4'-hydroxy-3',5'-di -tert-butylphenyl) propionate, tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl) propionate] methane; phosphite compounds include but are not limited to tris(2,4-di-tert-butylphenyl) phosphite, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl ester phosphite, tetrakis(2,4-di-tert-butylphenyl)[1,1-phenylene]-4,4'-diyl bisphosphite and bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite. In order to further improve the antioxidant performance of the film, preferably, based on 100 parts by weight of the polyolefin resin, the amount of the antioxidant in the above composition is 0.005 to 0.5 parts by weight, more preferably 0.01 to 0.4 parts by weight, more preferably 0.02 to 0.3 parts by weight, and even more preferably 0.03 to 0.2 parts by weight.

[0044] Ultraviolet light absorbers refer to substances that can absorb most of the ultraviolet energy and convert it into heat, thereby protecting certain electronic devices from being damaged by ultraviolet rays. In a preferred embodiment, the ultraviolet light absorber is selected from benzophenone and / or benzotriazole substances. More preferably, the ultraviolet light absorber includes but is not limited to 2-hydroxy-4-octyloxybenzophenone, 2,2-tetramethylenebis(3,1-benzoxazine-4-one), 2-(2'-hydroxy-5-methylphenyl)benzotriazole, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2-(2'-hydroxy-3',5'-di[1,1-dimethylphenyl]phenyl)-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole and 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)-benzotriazole. One or more of the group consisting of. In order to further improve the anti-ultraviolet performance of the formed film, in a preferred embodiment, based on 100 parts by weight of polyolefin resin, the amount of ultraviolet light absorber in the above composition is 0.05-0.5 parts by weight, more preferably 0.1-0.4 parts by weight, and further preferably 0.2-0.3 parts by weight.

[0045] Plasticizers can reduce the interaction between polymer molecules and the friction between polymer melt and metal surface during processing, so that the polymer plasticity is enhanced and processing is convenient. In a preferred embodiment, the plasticizer includes but is not limited to one or more of the group consisting of phthalate organic matter, aliphatic dibasic acid ester organic matter, phosphate organic matter, polyethylene wax organic matter and stearic acid organic matter; more preferably, the plasticizer includes but is not limited to one or more of the group consisting of polyethylene wax, trialkyl phosphate, triaryl phosphate, dioctyl sebacate, dioctyl adipate, dodecane dicarboxylate, dioctyl phthalate, dibutyl phthalate, stearic acid, zinc stearate and calcium stearate, and the number average molecular weight of the plasticizer is 2000-10000. In order to further improve the processing properties of the film, in a preferred embodiment, based on 100 parts by weight of polyolefin resin, the amount of plasticizer in the above composition is 0.01 to 5 parts by weight, more preferably 0.05 to 4 parts by weight, further preferably 0.1 to 3 parts by weight, and further preferably 0.3 to 2 parts by weight.

[0046] Pigments can color the encapsulation film and have light transmittance, so the encapsulated electronic devices can be made beautiful. Pigments include inorganic pigments and organic pigments, and can be selected from any one or more mixtures of iron nickel yellow, titanium chrome brown, cobalt green, iron red, iron yellow, cobalt blue, copper chrome black, ultramarine blue, indigo, cinnabar, realgar, cadmium red, cadmium yellow, iron blue, lithopone, iron oxide red, and iron oxide yellow.

[0047] In a preferred embodiment, based on 100 parts by weight of the polyolefin resin, the amount of the pigment in the above composition is 0.1 to 10 parts by weight, more preferably 0.5 to 8 parts by weight, further preferably 1 to 7 parts by weight, and further preferably 2 to 6 parts by weight.

[0048] The filler is an inorganic substance that can give the encapsulation film a reflective or light-absorbing property, and is preferably one or more of the group consisting of titanium dioxide, calcium carbonate, lithopone, aluminum oxide, aluminum-doped zinc oxide, indium tin oxide, antimony oxide, barium sulfate, montmorillonite, kaolin, talc, feldspar powder, and carbon black. In order to further improve the reflectivity of the film and thus improve the power of the electronic device, more preferably, the amount of the filler is 1 to 40 parts by weight, preferably 2 to 30 parts by weight, more preferably 3 to 20 parts by weight, and even more preferably 4 to 15 parts by weight.

[0049] In one embodiment of the present invention, the provided polyolefin composition is extruded through a screw extruder and cast through a T-shaped die to form a single-layer film. During the storage of the single-layer film, the bridging agent has good compatibility with the polyolefin resin, so the amount of migration to the surface of the film is small, which will not cause the film to become slippery, thereby preventing the film from moving relative to the substrate and electronic components during the laying process. The single-layer film is used for packaging electronic devices, such as Figure 1 As shown, a glass cover plate 1, a single-layer packaging film 2, an electronic component 3, a single-layer packaging film 2, and a polymer substrate 4 are stacked in this order, and laminated at 130 to 180° C. for 5 to 30 minutes using a vacuum laminator to finally form a complete electronic device module.

[0050] In another embodiment of the present invention, two or more screw extruders are co-extruded, wherein at least one screw extruder is used to extrude the polyolefin composition provided by the present invention, and another screw extruder is used to extrude other polymer materials, and other polymer materials are preferably polymers with polar groups, and the polar groups are selected from any one of carboxyl, ester group, hydroxyl, epoxy, amino, anhydride, and amide. In particular, the polymer with polar groups is selected from one of ethylene-vinyl acetate (EVA), ethylene-acrylic acid copolymer (EAA), and ethylene-methyl methacrylate copolymer (EMMA), and most preferably EVA. The materials extruded by multiple screws are cast by a T-die to form a multi-layer co-extruded film.

[0051] One beneficial effect of this solution is that the bridging agent in the polyolefin composition has good compatibility with the polyolefin resin and migrates less to the adjacent polar polymer layer, thereby ensuring sufficient cross-linking of the polyolefin resin.

[0052] The multi-layer co-extruded film is used for packaging electronic devices. The glass cover 1, the multi-layer co-extruded packaging film 5, the electronic component 3, the multi-layer co-extruded packaging film 5, and the polymer substrate 4 are stacked in this order, and laminated at 130-180° C. for 5-30 minutes by a vacuum laminator to finally form a complete electronic device module. Figure 2 At least one layer of the multi-layer co-extruded film 2 is formed by the polyolefin composition provided by the present invention. Preferably, the polyolefin composition layer provided by the present invention is an intermediate layer, which can give the co-extruded film better cross-sectional adhesion.

[0053] The beneficial effects of the present invention will be described below in conjunction with specific embodiments.

[0054] The test methods involved in the following embodiments are as follows:

[0055] 1. Cross-linking degree

[0056] According to the standard of GB / T 29848-2018, the obtained adhesive film was cut into a size of 10 cm×10 cm, and laminated using a laminating device at 150° C., vacuum for 5 minutes, and pressurized for 13 minutes to allow the adhesive film to undergo a cross-linking reaction.

[0057] Weigh about 1g of the laminated film. If it is a multi-layer co-extruded film, use a tool to peel off the polyolefin layer, weigh the polyolefin (so that the weighing value is A (g)), and perform Soxhlet extraction with boiling xylene for 5 hours.

[0058] After filtering with a 30-mesh stainless steel filter, the mesh was dried under reduced pressure at 145°C for 3 hours, the amount B (g) remaining on the mesh was calculated, and the degree of crosslinking was calculated using the following formula: Degree of crosslinking (weight %) = B / A x 100%.

[0059] 2. Bridging Agent Migration Assay

[0060] Before measuring the migration of the bridging agent, seal the 0.5mm thick packaging film in an aluminum-plastic bag and place it at a certain temperature for the required time. After the placement is completed, cut a 4cm×5cm sample (about 1g), soak it in 5mL of isopropanol, and then quickly ultrasonicate for 5 minutes. Collect the isopropanol soaking solution for Agilent 7890A gas chromatograph (analysis). If it is a multi-layer co-extruded film, after storage, use a tool to peel off the polyolefin layer, weigh 1g of polyolefin and soak it in 5mL of isopropanol for 24 hours, and then take the isopropanol soaking solution for Agilent 7890A gas chromatograph (analysis). Analyze the sample by GC according to the conditions in Table 1 below:

[0061] Table 1

[0062]

[0063]

[0064] The bridging agent in the isopropanol solution is calculated by a pre-established calibration curve. The calibration curve is established by plotting the signal response from the GC detector for isopropanol solutions of a certain bridging agent at several different concentrations. Subsequently, the concentration of the bridging agent in the sample solution can be determined by this pre-established curve. When the content of the bridging agent in the sample solution is known, the amount of bridging agent that migrates to the surface of the film or migrates to the adjacent polymer layer can be inferred, and the value is given in ppm of the weight of the polyolefin.

[0065] 3. Determination of friction coefficient

[0066] Cut the 0.5mm thick film into 7.5cm×10cm sheets, seal them in an aluminum-plastic bag, and place them at a specified temperature for a certain period of time. After storage, take out the film and test its dynamic friction coefficient on the PARAM MXD-02 instrument according to the ASTM D1894 standard. The specific operation is to place a 100g 7.5cm×7.5cm square weight on the film with the patterned surface of the film (with pyramid pattern) facing the clean embossed glass surface, and test the dynamic friction coefficient between the film and the glass by moving the glass horizontally, which is the ratio of the friction between the film and the glass to the weight of the weight. The smaller the value, the smaller the friction, indicating that the additive on the film surface has serious leakage.

[0067] 4. Adhesion strength measurement

[0068] Glass / film (two layers) / flexible backplane of 300mm×150mm are stacked in sequence and placed in a vacuum laminator, and laminated at 150℃ and 18 minutes to obtain a laminate. The flexible backplane / film is cut into 10mm±0.5mm specimens every 5mm in the width direction to test the adhesion between the film and the glass. According to the test method of GB / T 2790-1995, the peeling force between the film and the glass is tested on a tensile testing machine at a tensile speed of 100mm / min±10mm / min. The arithmetic average of three tests is taken as the peeling force of the film, accurate to 1N / cm.

[0069] 5. Component appearance evaluation

[0070] A 4-cell module is laminated in the order of glass, film, cell, film, and glass, and laminated using a vacuum laminator at 150°C, vacuuming for 5 minutes, and laminating for 13 minutes to make a double-glass solar module. The module is then placed in a PCT aging box for aging (temperature 121°C, relative humidity 100%), and the module is taken out after aging for 96 hours to observe its appearance.

[0071] Example 1

[0072] Weigh 0.05 parts of bridging agent octavinyl polysilsesquioxane and 0.7 parts of peroxide tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC), mix the two substances evenly, spray them into 100 parts of ethylene-octene copolymer POE particles (DOWEngage8669, melt index 14g / 10min, melting point 80°C) and stir until the surface of the POE particles is dry. Add the dried POE particles to a single-screw extruder, form a uniform POE melt through the melt shearing action of the screw, extrude it into a film through a wide-slit nozzle, form a texture structure on the surface of the film through the extrusion action of the embossing roller and the rubber roller, and then cool it through several cooling rollers, and finally wind it up through the winding roller. The thickness of the film is 0.5mm. Recorded as S1.

[0073] Examples 2 to 7 (Example abbreviated as S, for example, Example 1 abbreviated as S1), as well as Comparative Example 1 (C1) and Comparative Example 2 (C2) are implemented in the same manner as Example 1, and the proportions of the raw materials used are shown in Table 2.

[0074] Table 2 Composition of S1-S7, C1 and C2

[0075] S1 S2 S3 S4 S5 S6 S7 C1 C2 Engage 8669 100 100 100 100 100 100 TBEC 0.7 0.7 0.7 0.7 0.7 0.7 Octavidinyl polysilsesquioxane 0.05 3 1 Octallyl polysilsesquioxane 1 Octa(1-butenyl)polysilsesquioxane 1 Octa(1-pentenyl)polysilsesquioxane 1 Octa(1-hexenyl)polysilsesquioxane 1 Triallyl isocyanurate (TAIC) 1 Trimethylolpropane triacrylate (TMPTA) 1

[0076] The crosslinking behavior, adhesion behavior, additive migration behavior and friction coefficient of S1-S7, as well as C1 and C2 were analyzed using the test methods described above. The results are provided in Table 3 below.

[0077] Table 3 Test results of S1-S7, C1 and C2

[0078] S1 S2 S3 S4 S5 S6 S7 C1 C2 Crosslinking degree % 40.3 84 79.3 77.7 75 74.8 72 80 14.4 Adhesion strength to glass N / cm 42 126 107 98 90 87 87 6 5 Additive migration ppm (25℃, 4 weeks) 18 613 204 235 244 198 206 2657 6043 Friction coefficient (25℃, 4 weeks) 3.34 2.43 2.92 2.74 2.63 2.99 2.87 1.89 0.39

[0079] Example 8

[0080] Weigh 0.8 parts of bridging agent octavinyl polysilsesquioxane, 0.7 parts of peroxide tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC), 0.3 parts of γ-methacryloxypropyl trimethoxysilane (KH570), and 0.2 parts of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (Tinuvin 770), mix the above substances evenly, spray them into 100 parts of ethylene-octene copolymer POE particles (DOW Engage 8669, melt index 14 g / 10 min, melting point 80°C) and stir until the surface of the POE particles is dry.

[0081] The dried POE particles are added to a single-screw extruder, and the other two extruders extrude EVA (VA content 28wt%, MI 25), and then cast through the same die head to form an EVA / POE / EVA three-layer co-extruded film, in which POE is the middle layer and EVA is the upper and lower surface layers. The film is extruded by the embossing roller and the rubber roller to form a texture structure on the surface of the film, and then cooled by several cooling rollers, and finally wound by the winding roller. The thickness of the film is 0.5mm, and each layer is one-third thick. It is denoted as S9.

[0082] Examples 9 to 11 and Comparative Examples 3 and 4 were prepared in the same manner as Example 8 using EVA / POE / EVA three-layer co-extruded films, wherein the EVA layers were completely consistent and the formula of the POE layer was as shown in Table 4;

[0083] Table 4

[0084] S8 S9 S10 S11 C3 C4 Engage 8669 100 100 100 100 100 100 TBEC 0.7 0.7 0.7 0.7 0.7 0.7 KH570 0.3 0.3 0.3 0.3 0.3 Tinuvin 770 0.2 0.2 0.2 0.2 0.2 Octavidinyl polysilsesquioxane 0.8 Octallyl polysilsesquioxane 0.8 Octa(1-butenyl)polysilsesquioxane 0.8 Octa(1-hexenyl)polysilsesquioxane 0.8 Triallyl isocyanurate (TAIC) 0.8 Trimethylolpropane triacrylate (TMPTA) 0.8

[0085] The method described above was used to analyze the bridging agent content of S8-S11 and C3 and C4 intermediate layers, as well as the crosslinking degree of the intermediate layers and the appearance of the components. The analysis results are shown in Table 5:

[0086] Table 5

[0087]

[0088] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects: the bridging agent of the present invention can not only enable the polyolefin material to achieve sufficient cross-linking, but also overcome the technical problem in the prior art that the bridging agent has high viscosity and is easy to precipitate from the packaging material to the surface; in addition, this type of bridging agent also has a bonding effect, and is therefore particularly suitable for polyolefin packaging materials.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A packaging material, characterized in that: The packaging material is prepared from a polyolefin composition, which includes a polyolefin resin and a bridging agent, and the bridging agent has a structure shown in general formula (I): Wherein, n1, n2, n3, n4, n5, n6, n7, and n8 are each independently an integer of 0 to 6; in the polyolefin composition, based on 100 parts by weight of the polyolefin resin, the mass content of the bridging agent relative to the polyolefin resin is 0.05% to 3%; the polyolefin composition also includes 0.1 to 0.8 parts by weight of a tackifier, and the tackifier is a silane coupling agent having at least one ethylenically unsaturated group and at least one hydrolyzable group.

2. The packaging material according to claim 1, characterized in that: n1, n2, n3, n4, n5, n6, n7, and n8 are each independently 0 or 1.

3. The packaging material according to claim 1, characterized in that: The polyolefin resin is a homopolymer or copolymer of an alpha olefin having less than 20 carbon atoms, and the copolymer is a random copolymer or a block copolymer of two or more alpha olefins having less than 20 carbon atoms.

4. The packaging material according to claim 3, characterized in that: The alpha olefin having less than 20 carbon atoms is ethylene, propylene, butene, pentene, hexene, heptene or octene.

5. The packaging material according to claim 1, characterized in that: The polyolefin resin is ethylene vinyl acetate.

6. The packaging material according to claim 1, characterized in that: The melting point of the polyolefin resin is 40-100° C.; the melting index of the polyolefin resin is 1-30 g / 10 min.

7. The packaging material according to claim 1, characterized in that: The polyolefin composition further comprises an initiator, and the amount of the initiator is 0.1 to 1 part by weight based on 100 parts by weight of the polyolefin resin.

8. The packaging material according to claim 7, characterized in that: The initiator includes a photoinitiator or a peroxide.

9. The packaging material according to claim 1, characterized in that: Based on 100 parts by weight of the polyolefin resin, the polyolefin composition further comprises 0.01 to 5 parts by weight of an amide compound.

10. The packaging material according to claim 1, characterized in that: The polyolefin composition further comprises an auxiliary agent, wherein the auxiliary agent is one or more selected from the group consisting of a light stabilizer, an antioxidant, an ultraviolet absorber, a plasticizer, a pigment and a filler.

11. An electronic device module, comprising an electronic component and one or more layers of packaging material, characterized in that: The packaging material is the packaging material according to any one of claims 1 to 10.

12. The electronic device module according to claim 11, characterized in that: The electronic component is a solar cell.

13. The electronic device module according to claim 11, characterized in that: The packaging material is a packaging film, and the packaging film is a non-cross-linked film or a pre-cross-linked film. When the packaging film is a pre-cross-linked film, the pre-cross-linking degree of the pre-cross-linked film is 1% to 80%.